Pancasila as Main Reference of Ideology for Indonesian Legal Reform - Rodiyah, Rodiyah (Law Research Review Quarterly, 2016)
The implementation of Pancasila in the context of Indonesian state life includes two things. First, it describes the basic values ​​of Pancasila into state ethical norms which contain a set of five basic ideas that can be a source of inspiration and solutions for the problems of Indonesian nationality. Second, it describes the five basic values ​​of Pancasila into the norms of state law, namely the rules of state legislation where the contents of the material do not conflict with Pancasila itself. The context of this implementation is that Ideology is the center for Indonesian Legal Reform. The renewal of Indonesian law was born in the nation's historical dynamics which have always sought Indonesian law based on the reality of the legal needs of Indonesian people who are plural in homogeneity of diversity. The reality which shows that it is not easy to reach legal ontology, namely justice and prosperity, in the development of Indonesian law through legal stages in the substance of civil law law in the reform era (first amendment) in Article 1 of the 1945 Constitution by adopting common law. Some alternative directions for Indonesian law in the context of reform are to combine several values ​​of the legal system. The author concludes that based on the ideology of Pancasila, the Qibla of Indonesian Legal Reform is more than Progressive Law which is based on the Humanitarian God of Deliberation and Social Justice.